2021
DOI: 10.1021/acs.jafc.1c04585
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Effects of Volatiles Produced by Bacillus tequilensis XK29 against the Black Spot Disease Caused by Ceratocystis fimbriata in Postharvest Sweet Potato

Abstract: Black spot disease caused by Ceratocystis fimbriata is destructive to the production, transportation, and storage of sweet potato. The antifungal effects of Bacillus tequilensis XK29 against C. fimbriata through volatile organic compounds (VOCs) were evaluated in this study. The activated carbon assay proved that XK29 could exert antibiotic effects through volatiles. By optimizing the wheat seed weight, inoculation method, concentration, volume, and time, the antifungal activity of XK29 was significantly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Compared with other crops, sweetpotatoes can support more people per unit of land, and they are the staple food for large populations over the world [5]. However, sweetpotatoes are prone to diseases during postharvest storage and transportation, such as black rot [6], soft rot [7], and root rot [8]. Among them, black rot is the most typical.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other crops, sweetpotatoes can support more people per unit of land, and they are the staple food for large populations over the world [5]. However, sweetpotatoes are prone to diseases during postharvest storage and transportation, such as black rot [6], soft rot [7], and root rot [8]. Among them, black rot is the most typical.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that B. tequilensis can quickly and stably colonize plants, and has a high propagation rate and a strong proliferative capacity [ 30 ]. B. tequilensis has high efficiency and broad-spectrum resistance to plant pathogens, has a combined treatment effect on plant diseases such as anthracnose [ 31 ] and black spot disease [ 32 ], has a high prevention effect, and has good application prospects for the prevention and control of plant diseases [ 33 ]. However, it has never been reported for γ-PGA production; therefore, B. tequilensis BL01 was selected for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that B. tequilensis can quickly and stably colonize plants, and has a high propagation rate and strong in proliferative capacity (Shultana et al 2021). B. tequilensis has high e ciency and broad-spectrum plant pathogen resistance, has a combined treatment effect on plant diseases such as anthracnose (Kwon et al 2022) and black spot disease (Xu et al 2021), has a high prevention effect, and has good application prospects for the prevention and control of plant diseases (Guerrero-Barajas et al 2020). However, it has never been reported for γ-PGA production; therefore, B. tequilensis BL01 was selected for subsequent experiments.…”
Section: Screening Of Highly γ-Pga-producing Strainsmentioning
confidence: 99%